PENGARUH INFLUENCER TIKTOK TERHADAP MINAT BELI PRODUK FORE COFFE PADA GENERASI Z DI SURABAYA DENGAN CUSTOMER REVIEW SEBAGAI VARIABEL MODERASI - Salman Al Farisi, Muhammad; Amriel, Egan Evanzha Yudha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
TikTok influencers and customer reviews often provide different perspectives on a product, thereby influencing the formation of Generation Z’s purchase intent. This study aims to explore the influence of TikTok influencers on Generation Z’s purchase intent for Fore Coffee products in Surabaya, with customer reviews serving as a moderating variable. The method used in this study is a quantitative approach through the distribution of questionnaires to 120 respondents belonging to Generation Z in Surabaya. For data analysis, Structural Equation Modeling-Partial Least Squares (SEM-PLS) was used with the support of the SmartPLS 4.0 application. The findings indicate that TikTok influencers have a positive and significant influence on the purchase intention for Fore Coffee products. Customer reviews have a positive and significant effect on purchase intention, although their moderating role is weak. This study is expected to serve as a reference for companies in improving their digital marketing strategies through the use of TikTok influencers and customer reviews. Future research is encouraged to include additional variables that influence purchase intention, as well as expand the number of respondents and the study area so that the results obtained are more representative and reflect consumer behavior more comprehensively.